Community Readiness for Plastic Waste Reduction Through Recycled Craft-Making: A Case Study in Parit Jelutung, Batu Pahat, Johor - Farisha Nadzirah Abd Malek; Roslinda Ali; Mohammad Asraff Jailani (Progress in Engineering Application and Technology, 2026)
Plastic waste management remains a critical environmental challenge in Malaysia due to increasing plastic consumption, rising waste generation, and limited sustained public participation in sustainable practices. This study examines community readiness for plastic waste reduction through recycled craft-making activities as a practical, community-based approach in Parit Jelutong, Batu Pahat, Johor. A recycled plastic craft-making demonstration programme was conducted to provide hands-on exposure, followed by a questionnaire survey involving students, teachers, and members of the Parent–Teacher Association. A quantitative approach was adopted, and the data were analysed using descriptive analysis, reliability test, and the Mann–Whitney U test to examine differences in awareness based on respondents’ demographic characteristics and programme participation. The results indicate that respondents generally demonstrated positive perceptions towards recycled craft-making activities, particularly in relation to plastic waste reduction and potential economic value. However, the analysis revealed no significant differences in awareness levels based on respondents’ status, gender, or attendance at the demonstration programme. Feedback from respondents showed strong support for expanding recycled craft-making initiatives to a wider community, although willingness to invest financially in recycled products or paid training programmes remained moderate. Overall, the findings suggest that while recycled craft-making activities are well accepted, sustained engagement and continuous practical exposure are essential to strengthen long-term awareness and promote behavioural change in plastic waste management.